Teaching staff the rules of feeding is an obligatory aspect of speech therapy work to overcome post-stroke dysphagia - O. D. Larina; Yu. Yu. Rudometova; T. V. Novikova (Лечащий Врач)
The article is devoted to the issues of awareness of members of a multidisciplinary rehabilitation team and caregivers about the requirements for organizing oral nutrition of patients with moderate and mild post-stroke dysphagia at the first stage of medical rehabilitation. Dysphagia increases the risk of complications such as aspiration pneumonia, dehydration, malnutrition, and is the most common cause of death. The federal clinical guidelines for the diagnosis and treatment of dysphagia in diseases of the central nervous system of the Union of Rehabilitologists of Russia describe methods for the diagnosis, treatment, rehabilitation and prevention of dysphagia. However, practice has shown that not all specialists working in the care system for patients with post-stroke dysphagia are familiar with clinical recommendations. Insufficient awareness of the staff caring for patients with dysphagia required the creation of materials regulating the standards for managing patients with dysphagia. Timely diagnosis of swallowing disorders, determination of nutritional status, choice of feeding method, and most importantly, compliance with the rules for organizing the process of taking liquid, solid (including tableted) food orally can prevent complications of dysphagia, increase the effectiveness of oral intake of nutrients, thereby expanding the possibilities for rehabilitation. measures for patients with consequences of strokes. A wide range of specialized food products on the domestic market provides an optimal way of eating. The purpose of the study was to analyze and test the use of visual information materials on the requirements for compliance with food intake recommendations during the first stage of medical rehabilitation. The article describes the experience of applying personalized requirements for safe nutrition for 56 patients with post-stroke dysphagia, who are fed through a nasogastric tube. The degree of dysphagia was assessed using the volume-viscosity swallow test (V-VST) and the Modified Swallowing Test (Modified MANN Assessment of Swallowing Ability). The study was conducted from March to November 2021. Proper organization of care for patients with dysphagia and taking into account the recommendations of a speech therapist made it possible to transfer patients to oral nutrition. Thus, the use of visual personalized methods of informing caregivers of patients with post-stroke dysphagia about the features of care and nutrition can reduce or completely eliminate swallowing disorders, shorten rehabilitation periods and improve the quality of life of patients.